Mathematics Learning Difficulties in Distance Learning - Budi Murtiyasa; Almas Husna Nurul Lathifah (JETL (Journal of Education, Teaching and Learning), 2023)
Some students feel that mathematics is less fun because the students lack basic knowledge of mathematics which leads to a lack of confidence in learning. Especially during the COVID-19 outbreak, distance learning was needed, including mathematics, and many students had difficulties in learning. Learning difficulties that arise during distance learning can interfere with the subsequent learning process and have a significant impact on the students' academic performance in mathematics. This study aims to determine the students' mathematics learning difficulties in distance learning at Junior High School 13 Surakarta. The method used in this research is descriptive qualitative. Qualitative descriptive research aims to describe student learning difficulties during the pandemic with the distance learning system. The subjects of this study were students of eighth grade of Junior High School 13 Surakarta. Data collection techniques used are interviews and observation. The interview method used was a guided free interview which was then analyzed using an interactive model. Based on the results of the analysis of student learning difficulties in distance learning mathematics caused by several factors, namely internal and external factors. Internal factors, namely those that come from within the student, include the lack of interest and motivation of students to take part in online mathematics learning. While external factors are factors that come from within students, including difficulties in understanding the material provided by the teacher rather than in detail, unstable internet network, student learning environment that does not support learning, motivation, and encouragement from parents or closest family.